Failure Mechanisms of Nanoparticle Reinforced Metal Matrix Composite - Basak, A.; Pramanik, Alokesh; Islam, Mohammad Nazrul (Trans Tech Publications Inc, 2013)
The quest for the advanced functional material of superior functionality for advanced structure is being driven in various fronts of engineering materials. One of such front is metal matrix composite (MMC) which has already been proven as one of the most productive field in that respect. With the advance of technology, now it is possible to reinforce the MMCs with nano-sized particles compared to conventional micron-sized ones. However, the addition of nanoparticle in the MMC to improve its mechanical properties is not unconditional. To achieve positive gain by adding nanoparticles in the MMCs, all the influencing factors should be taken into consideration. The present paper reviews the failure mechanisms of nanoparticles reinforced MMCs in light of its strengthening mechanisms.